Nivolumab for relapsed or refractory Hodgkin lymphoma: real-life experience - (:unkn) unknown (SPRINGER, 2020)
Classical Hodgkin lymphoma (cHL) is considered a curable disease; however, in approximately one-third of the responding patients, the disease relapses following completion of therapy. One of the drugs that have been approved for the treatment of relapsed/refractory cHL is nivolumab, an immune check point inhibitor that shows its effects by blocking the programmed death 1 (PD-1) receptor. In this study, we present a retrospective real-life analysis of the usage of nivolumab in patients with relapsed/refractory cHL that have joined the named patient program (NPP) for nivolumab, reflecting 4 years of experience in the treatment of relapsed/refractory cHL. We present a retrospective analysis of 87 patients (median age, 30) that participated in the NPP in 24 different centers, who had relapsed/refractory cHL and were consequently treated with nivolumab. The median follow-up was 29 months, and the median number of previous treatments was 5 (2-11). In this study, the best overall response rate was 70% (CR, 36%; PR, 34%). Twenty-eight of the responding patients underwent subsequent stem cell transplantation (SCT). Among 15 patients receiving allogeneic stem cell transplantation, 9 patients underwent transplantation with objective response, of which 8 of them are currently alive with ongoing response. At the time of analysis, 23 patients remained on nivolumab treatment and the rest discontinued therapy. The main reason for discontinuing nivolumab was disease progression (n = 23). The safety profile was acceptable, with only nine patients requiring cessation of nivolumab due to serious adverse events. The 24-month progression-free and overall survival rates were 58.5% (95% CI, 0.47-0.68) and 78.7% (95% CI, 0.68-0.86), respectively. Eighteen patients died during the follow-up and only one of these was regarded to be treatment-related. With its efficacy and its safety profile, PD-1 blockers became an important treatment option in the heavily pretreated cHL patients.
Keywords: Hodgkin lymphoma; Resistant; relapsed disease; Programmed death 1 (PD-1) blocker; Nivolumab; BRENTUXIMAB VEDOTIN; PHASE-II; CELL TRANSPLANTATION; RESPONSE CRITERIA; PEMBROLIZUMAB; MULTICOHORT; EFFICACY; BLOCKADE; FAILURE; ABVD